Development of Probability Learning Media PjBL-STEM Based Using E-comic to Improve Students’ Literacy Numeracy Skills - Gita Mulya Aprilia; Hasna Nabila; Risma Mutiara Karomah; Elyza Irmawati HS; Shinta Nuriyah Permadani; Farida Nursyahidah (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
This research is motivated by the fact that there are still many students who find it difficult to learn the probability material, which affects the students' low literacy numeracy ability. One of the efforts to improve students' literacy and numeracy skills is to innovate interactive learning media and the right approach. Therefore, this study develops interactive learning media in the form of e-comic based on Science Technology Engineering Mathematics (STEM). This research is a type of development research with the ADDIE model which has 5 stages including Analysis, Design, Development, Implementation, and Evaluation. This article will discuss Analysis, Design, and Development due to time constraints. The subjects in this study were two material experts and two media experts. This study used a data collection instrument in the form of a questionnaire. Validation of data from experts will be analyzed using qualitative descriptive analysis and quantitative descriptive analysis. The results of the validation data were calculated using the mean formula. Validation of literacy numeracy ability to get a score of 3.5 with very good qualifications and material validation to get a value of 3.8 with very good qualifications. So that the PjBL-STEM-based interactive e-comic learning media can be declared valid, practical, and effective to improve students' literacy numeracy skills and have very good qualifications. The development of interactive learning media can then be implemented in the classroom to determine the effect of media on students' literacy skills and as a reference for educators to develop interactive learning media with other PjBL-STEM to improve students' literacy skills.Penelitian ini dilatarbelakangi oleh masih banyaknya siswa yang merasa kesulitan dalam mempelajari materi probabilitas, hal ini berdampak pada rendahnya kemampuan literasi numerasi siswa. Salah satu upaya untuk meningkatkan kemampuan literasi numerasi siswa adalah dengan melakukan inovasi media pembelajaran interaktif dan pendekatan yang tepat. Oleh karena itu, penelitian ini mengembangkan media pembelajaran interaktif berupa e-comic berbasis Science Technology Engineering Mathematics (STEM). Penelitian ini merupakan jenis penelitian pengembangan dengan model ADDIE yang memiliki 5 tahapan yaitu Analisis, Perancangan, Pengembangan, Implementasi, dan Evaluasi. Artikel ini akan membahas Analisis, Desain, dan Pengembangan karena keterbatasan waktu. Subjek dalam penelitian ini adalah dua orang ahli materi dan dua orang ahli media. Penelitian ini menggunakan instrumen pengumpulan data berupa angket. Validasi data dari ahli akan dianalisis menggunakan analisis deskriptif kualitatif dan analisis deskriptif kuantitatif. Hasil validasi data dihitung dengan menggunakan rumus mean. Validasi kemampuan literasi berhitung mendapatkan nilai 3.5 dengan kualifikasi sangat baik dan validasi materi mendapatkan nilai 3.8 dengan kualifikasi sangat baik. Sehingga media pembelajaran e-comic interaktif berbasis PjBL-STEM dapat dinyatakan valid, praktis, dan efektif untuk meningkatkan kemampuan literasi berhitung siswa dan memiliki kualifikasi sangat baik. Pengembangan media pembelajaran interaktif selanjutnya dapat diimplementasikan di dalam kelas untuk mengetahui pengaruh media terhadap kemampuan literasi numerasi siswa dan sebagai acuan bagi pendidik untuk mengembangkan media pembelajaran interaktif dengan PjBL-STEM lainnya untuk meningkatkan kemampuan literasi numerasi siswa.